Elaboración del estudio de prefactibilidad para la construcción de la red del suministro de gas natural de la vereda el chorrito en el municipio de Tibasosa, Boyacá. (2017)
This document presents the "Pre-feasibility study for the construction Of the natural gas supply network of El Chorrito in the municipality Of Tibasosa, Boyacá. " The document contains the information of the project, in which the profile is elaborated, The Strategic Identification and Alignment of the Project (IAEP), the formulation (Market, technical, environmental, administrative, cost and Benefits, budget, investment and financial), project evaluation and Management plan.